UCSF LEaP (Learning From Your Experiences as a Professional): Guidelines for Critical Reflection - Louise Aronson; Marieke Kruidering; Brian Niehaus; Patricia O'Sullivan (Association of American Medical Colleges, 2012)
Abstract Introduction Since the late 1990s, accrediting bodies and oversight organizations have recognized reflection as an essential skill for health professionals and an important tool for competency-based assessment. As a result, educators and clinicians across the medical education spectrum are looking for guidance in the teaching and development of reflective ability. Based on a literature review and survey, we developed a consensus definition of reflection, and created the Learning From Your Experiences as a Professional (LEaP) Guidelines; a brief, stand-alone guide for both medical students and faculty. Methods The guidelines resource is a three-page document. The first page includes student instructions on the effective use of reflection. Page two consists of a reflective exercise modeled on the clinical SOAP (Chief Complaint/Identification, Subjective, Objective, Assessment, and Plan) note. Page three concludes with a review of frequently asked questions. The resource takes approximately 1 hour to administer. Results We conducted a randomized trial of the LEaP guidelines with third-year medical students at the University of California, San Francisco. We assigned half our sample of 167 students to receive the LEaP guidelines and half to receive only a definition of critical reflection in medical education. We found that the LEaP guidelines improved performance. Mean reflection scores were 3.81 (SD = 1.9) using LEaP guidelines and 2.22 (SD = .89) without the guidelines (p < 0.001). Discussion In reflective learning, as in clinical practice, it appears that guidelines improve performance. Although to date more work has been done on assessing reflection skills in learners, it stands to reason that teaching the characteristics of more effective reflection and helping learners acquire the skills to reflect well should occur in conjunction with evaluations of their ability to do so. Questions remain about the dose and timing of instruction and guideline guided exercises needed to develop reliable reflective skill.